2020
DOI: 10.3390/microorganisms8101571
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba castellanii as a Screening Tool for Mycobacterium avium Subspecies paratuberculosis Virulence Factors with Relevance in Macrophage Infection

Abstract: The high prevalence of Johne’s disease has driven a continuous effort to more readily understand the pathogenesis of the etiological causative bacterium, Mycobacterium avium subsp. paratuberculosis (MAP), and to develop effective preventative measures for infection spread. In this study, we aimed to create an in vivo MAP infection model employing an environmental protozoan host and used it as a tool for selection of bacterial virulence determinants potentially contributing to MAP survival in mammalian host mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Few studies have related MAP association with amoebae. Among them, it was shown that incubation of MAP with Acanthamoeba polyphaga and Acanthamoeba castellanii, led to a decreasing MAP number in the first few post-internalization days, but increased after an extended period of several weeks (Mura et al, 2006;Whan et al, 2006;Phillips et al, 2020). Our results provide evidence that MAP can also persist for at least for 3 days in association with R. vilicus.…”
Section: Rosculus Vilicus Interacts With Map For At Least a Few Dayssupporting
confidence: 55%
“…Few studies have related MAP association with amoebae. Among them, it was shown that incubation of MAP with Acanthamoeba polyphaga and Acanthamoeba castellanii, led to a decreasing MAP number in the first few post-internalization days, but increased after an extended period of several weeks (Mura et al, 2006;Whan et al, 2006;Phillips et al, 2020). Our results provide evidence that MAP can also persist for at least for 3 days in association with R. vilicus.…”
Section: Rosculus Vilicus Interacts With Map For At Least a Few Dayssupporting
confidence: 55%
“…FLA have many innate immunity mechanisms to defend against intracellular microbial infections and facilitate the consumption of these microbes, such as phagosome maturation, lysosomal degradation, acidification, and reactive oxygen species production (Phillips et al, 2020). Furthermore, previous studies have highlighted the similarities between amoebae and macrophages (Al-Antary, 2021; Lertjuthaporn et al, 2022).…”
Section: Fla As Biological Reservoirs and Vectors Of Pathogensmentioning
confidence: 99%
“…Amoebae may act as catalysts of genetic modification, allowing MAP to develop phenotypes different from those expressed in the culture medium (Partridge, 2005). These modified MAP phenotypes alter antibiotic resistance and virulence (Phillips et al, 2020).…”
Section: Examples Of Bacterial Endosymbionts Of Acanthamoebamentioning
confidence: 99%
See 1 more Smart Citation
“…A. castellanii can also host Legionella ( Swart et al, 2018 ; Nomura et al, 2022 ), Vibrio cholerae , Francisella tularensis ( Abd et al, 2003 ) and the causative agent of Johne’s disease, Mycobacterium avium subsp. paratuberculosis (MAP) ( Phillips et al, 2020 ). These bacteria have been referred to as amoeba-resistant bacteria.…”
Section: Acanthamoeba Related Diseasesmentioning
confidence: 99%